Assessment of the status of malnutrition and immunization coverage in under-five children attending Anganwadis - Singh, Mahima; Yadav, Prajwal; Rehan, Rimsha; Chowdhury, Shubhayu Roy; Vaidya, Varsha M; Patil, Reshma S; Patil, Karamchand H (Indian Journal of Child Health, 2020)
Background: Malnutrition affects people worldwide. Immunization is the most cost-effective and accessible health investment which if taken efficiently can prevent a vast spectrum of diseases in children. Aim: The focus of this study is to assess the nutrition status and immunization coverage of children attending various Anganwadis. Materials and Methods: A study of immunization and nutrition status was held among 252 children under the age of 5, attending 30 Anganwadis in Western India. Results: This study showed that 27.12% of female and 38.94% of male children fell under malnutrition status, including both moderate and severe category. About 72% of children completed their vaccination schedule, as compared to 14% of children with incomplete immunization. The remaining 14% lacked complete records. Conclusion: Our study showed a smaller proportion of children under severe and moderate acute malnutrition compared to other settings. A few dietary modifications and counseling can give us a better future scenario.